Question #e4173

1 Answer
Apr 30, 2017

Answer:

The current gain is #beta = 49#

Explanation:

Given: #I_0/I_E =0.98" [1]"#

We know that the output current is the current gain #beta# multiplied by the base current:

#I_0 = betaI_b" [2]"#

We know that the emitter current is the output current plus the base current:

#I_E = I_0+ I_b#

#I_E = betaI_b+ I_b" [3]"#

Substitute equations [2] and [3] into equation [1]:

#(betaI_b)/(betaI_b+I_b) = 0.98#

#beta/(beta+1) = 0.98#

#1 -1/(beta+1) = 0.98#

beta+1 = -1/(0.98-1)

#beta+1 = 50#

#beta = 49#